2009
DOI: 10.1519/jsc.0b013e3181a00d98
|View full text |Cite
|
Sign up to set email alerts
|

Forward Lunge: A Training Study of Eccentric Exercises of the Lower Limbs

Abstract: A few studies have shown that eccentric exercise is effective for prevention and treatment of muscle injuries. Most earlier studies on eccentric exercises have used training with advanced equipment. Forward lunges are considered eccentric exercises, and they may be performed without any equipment. These exercises are commonly used by sprint runners. We performed a prospective, randomized, 6-week training study comparing the effects of walking or jumping forward lunges on hamstring and quadriceps strength and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…A recent review study demonstrated that squats and plyometric exercises can improve vertical jump height (de Villarreal, Kellis, Kraemer, & Izquierdo, 2009). Furthermore, performing squat and walking lunge exercises can be eff ective in increasing vertical jump height (Jönhagen, Ackermann, & Saartok, 2009;Wisløff , Castagna, Helgerud, Jones, & Hoff , 2004). Th us, the underlying eff ectiveness of the FIFA 11+ programme on vertical jump performance may be caused by using core, plyometric, and jump exercises.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review study demonstrated that squats and plyometric exercises can improve vertical jump height (de Villarreal, Kellis, Kraemer, & Izquierdo, 2009). Furthermore, performing squat and walking lunge exercises can be eff ective in increasing vertical jump height (Jönhagen, Ackermann, & Saartok, 2009;Wisløff , Castagna, Helgerud, Jones, & Hoff , 2004). Th us, the underlying eff ectiveness of the FIFA 11+ programme on vertical jump performance may be caused by using core, plyometric, and jump exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Goodmornings start in an upright standing position and, with the barbell on the shoulders, the hips are progressively flexed until maximum hip flexion is reached where the curvature of the lower spine remains in the lordosis, but the knees remain straight throughout. Similarly, split squats are performed with the barbell on the shoulders, but one foot is placed in an anterior position while the participant flexes the knees as far as possible [22]. Deadlifts, goodmornings and split squats are thought to be comparable in their ability to train strength, speed and power in all sport types [23], as well as for improving joint stability in anterior cruciate ligament (ACL) rehabilitation [24, 25], but also with respect to their potential for injury of the lower limbs and the back while performing the exercises [26].…”
Section: Introductionmentioning
confidence: 99%
“…In function, however the hamstrings also act to control and decelerate the limb (as in kicking a football), act antagonistically to the rectus femoris to prevent hip flexion (as in squatting or jumping), and act as an ACL agonist by preventing anterior tibial translation (Li et al 1999;Ebben and Leigh 2000). Movements that target these attributes may include Nordic hamstring lowers (Fig 3.8a, 3.8b) (Askling et al 2003;Mjolsnes et al 2004;Clark et al 2005;Arnason et al 2007), drop jump landings (including correct landing during plyometric activity) and lunges (Jonhagen et al 2009), increasing progressively in terms of both velocity and amplitude. Eccentric and plyometric training has also been shown to decrease the risk/incidence of both ACL and hamstring strain injuries (Hewett et al 1996;Heidt et al 2000;Clark et al 2005;Mjolsnes et al 2004;Wilkerson et al 2004;Hewett et al 2005;Mandelbaum et al 2005;Myer et al 2005).…”
Section: Muscle Actionmentioning
confidence: 99%